098 Hyperestrogenism is Associated with Sexual Function Impairment in Men – Findings from a Cross-Sectional, Real-Life Study. (1st May 2022) - Boeri, L; Capogrosso, P; Cazzaniga, W; Candela, L; Fallara, G; Pozzi, E; Belladelli, F; Schifano, N; Cignoli, D; Colandrea, G; Abbate, C; Montorsi, F; et al.
ABSTRACT: Introduction: High serum estrogens levels have been associated with higher rates of heart attacks, strokes, and prostate cancer. Moreover, hyperestrogenism is believed to be harmful to male sexuality. Objectives: We aimed to investigate the prevalence of and the impact of hyperestrogenism on sexual functioning in a cohort of men seeking medical attention for new onset erectile dysfunction (ED) in the real-life setting. Methods: Data from 481 men seeking first medical help for new-onset ED at a single andrology centre were analyzed. Patients were assessed with a thorough medical and sexual history. Comorbidities were scored with the Charlson Comorbidity Index (CCI). All patients completed the International Index of Erectile Function (IIEF) and the IIEF-Erectile function (IIEF-EF) domain was categorized according to Cappelleri's criteria. Circulating hormones were measured in every patient. Hyperestrogenism was defined as estrogen (E2) levels >42.6 pg/mL (Tan RS et al. 2015). Descriptive statistics and logistic/linear regression models tested the association between hyperestrogenism and IIEF scores. Results: Overall, 88 (18.3%) patients had serum estrogen levels suggestive for hyperestrogenism. Men with hyperestrogenism were older [median (IQR) 46 (34-58) vs. 44 (32-55) years; p<0.001], had more comorbidities [CCI≥2: 18 (20.5%) vs. 28 (7.1%); p<0.001] and higher serum testosterone (TT) levels [5.4 (4.2-7.3) vs. 4.3 (3.1-5.7); p=0.02] than those with normal E2 values. A higher rate of severe ED was found in men with elevated E2 levels (48.9% vs. 30%; p=0.02). Moreover, the IIEF-orgasmic function (IIEF-OF) domain was lower in ED men with hyperestrogenism than those with normal E2 values [6 (3-10) vs. 9 (6-10), p=0.03]. Serum E2 levels were positively correlated with TT levels (rho 0.25, p<0.001), but negatively correlated with IIEF-OF scores (rho -0.17, p=0.005) and IIEF-EF scores (rho -0.32, p<0.001) (Figure 1). At multivariable logistic regression analysis, hyperestrogenism (OR 2.37, p=0.03) was associated with severe ED after accounting for age, BMI, CCI and serum T values. Conclusions: One out of five men seeking first medical help for ED showed elevated serum E2 values in the real-life setting. Hyperestrogenism was associated with health significant comorbidities, orgasmic function impairment and higher severity of ED. Disclosure: Work supported by industry: no.